A comparison of the prognostic performance of the Lugano 2014 and RECIL 2017 response criteria in patients with NHL from the phase III GOYA and GALLIUM trials - Lale Kostakoglu; Maurizio Martelli; Laurie H. Sehn; Andrew Davies; Marek Trněný; Michael Herold; Umberto Vitolo; Wolfgang Hiddemann; Judith Trotman; Andrea Knapp; Federico Mattiello; Tina G. Nielsen; et al. (eJHaem, 2023)
Abstract The Lugano 2014 criteria are the standard for response assessment in lymphoma. We compared the prognostic performance of Lugano 2014 and the more recently developed response evaluation criteria in lymphoma (RECIL 2017), which relies primarily on computed tomography and uses unidimensional measurements, in patients with previously untreated diffuse large B‐cell lymphoma (DLBCL) and follicular lymphoma (FL) from the phase III GOYA and GALLIUM trials, respectively. Concordance between responses according to the Lugano 2014 and RECIL 2017 criteria was analyzed. Landmark analyses of progression‐free survival (PFS) and overall survival (OS) by end of treatment (EOT) and end of induction (EOI) response status according to RECIL 2017 and Lugano 2014 criteria, and prognostic value of response at EOT/EOI were also compared. Overall, 1333 patients were included from GOYA and 502 from GALLIUM. Complete response (CR) status according to RECIL 2017 criteria showed high concordance with complete metabolic response (CMR) status by Lugano 2014 criteria in both GOYA (92.5%) and GALLIUM (92.4%). EOT and EOI CR/CMR status by both criteria was highly prognostic for PFS in GOYA (RECIL 2017 [CR]: hazard ratio [HR], 0.35 [95% confidence interval [CI] 0.26–0.46]; Lugano 2014 [CMR]: HR, 0.35 [95% CI 0.26–0.48]; both p < .0001) and GALLIUM (RECIL 2017 [CR]: HR, 0.35 [95% CI 0.23–0.53]; Lugano 2014 [CMR]: HR, 0.21 [95% CI 0.14–0.31]; both p < .0001). In conclusion, response categorization by RECIL 2017 is similar to that by Lugano 2014 criteria, with high concordance observed. Both were prognostic for PFS and OS.